Respuesta :
Answer:
[tex](x+ \boxed{-5})^2+(y+\boxed4)^2=\boxed{100}[/tex]
Step-by-step explanation:
Given:
Center of circle is at (5, -4).
A point on the circle is [tex](x_1,y_1)=(-3, 2)[/tex]
Equation of a circle with center [tex](h,k)[/tex] and radius 'r' is given as:
[tex](x-h)^2+(y-k)^2=r^2[/tex]
Here, [tex](h,k)=(5,-4)[/tex]
Radius of a circle is equal to the distance of point on the circle from the center of the circle and is given using the distance formula for square of the distance as:
[tex]r^2=(h-x_1)^2+(k-y_1)^2[/tex]
Using distance formula for the points (5, -4) and (-3, 2), we get
[tex]r^2=(5-(-3))^2+(-4-2)^2\\r^2=(5+3)^2+(-6)^2\\r^2=8^2+6^2\\r^2=64+36=100[/tex]
Therefore, the equation of the circle is:
[tex](x-5)^2+(y-(-4))^2=100\\(x-5)^2+(y+4)^2=100[/tex]
Now, rewriting it in the form asked in the question, we get
[tex](x+ \boxed{-5})^2+(y+\boxed4)^2=\boxed{100}[/tex]